ANALISIS BUTIR SOAL UJIAN MASUK MANDIRI UIN ALAUDDIN MAKASSAR DENGAN TEORI TES MODERN: ITEM ANALYSIS OF UIN ALAUDDIN MAKASSAR INDEPENDENT ENTRANCE EXAMINATION QUESTIONS WITH MODERN TEST THEORY - Andi Kusumayanti; Nur Jannah (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to find out how the quality of UMM UIN Alauddin Makassar questions in 2021 in the field of mathematics with the modern test method of the 2-PL model with indicators of difficulty level and differentiating power. This study is a quantitative analysis that emphasizes the analysis of the characteristics of the items empirically. The subjects of the research were the participants of the UIN Alauddin Makassar Independent Entrance Exam in 2021. The objects selected were multiple-choice math questions made by the UMM Alauddin Makassar UMM Question Making Team which consisted of 8 question packages with 5 items for each package. The method used in data collection is the documentation method, by collecting student responses to the 2021 UMM UIN Alauddin Makassar problem in mathematics made by the UMM Alauddin Makassar UMM Question Making Team, which is then analyzed quantitatively based on modern test methods. Based on the results of data analysis using the RStudio application, it is known that the items for the 2021 UIN Alauddin Makassar Independent Entrance Exam, based on the level of difficulty, obtained: (1) easy category items as many as 2 items, namely items number 4 and 5, (2) items very easy category questions as many as 3 items, namely items number 1, 2 and 3. Furthermore, in terms of discriminating power, obtained: (1) very bad category items as many as 3 items, namely item numbers 3, 4 and 5, (2 ) items in the bad category as many as 2 items, namely items number 1 and 2. Thus, it can be stated that overall the questions for the 2021 Alauddin UIN Makassar Mandiri Entrance Exam are not good.